Prospects of cooperation of the state-owned electric power industry of Russia for realization of innovative programs - V N Aleksandrov (RUDN Journal of Economics, 2013)
The article is devoted to the purpose of the innovative programs of 2 monopolies of power industry-FGC UES and JSC «so UES». Sets the framework of scientific-technical cooperation and external organizations with which interact with the named companies. Are the documents initiating the creation of technological platforms and the degree of participation of the companies in them. Determined that both companies are involved in the technological platform of «Intelligent energy system of Russia». In conclusion, identified the main enterprise, which will be implemented most of the R & d of the companies and provides a list of the main problems and threats facing the industry in connection with the fulfilment of the feast.